From Parents to Peers: Trajectories in Sources of Academic Influence Grades 4 to 8. (December 2017) - Sorensen, Lucy C.; Cook, Philip J.; Dodge, Kenneth A.
Prior research and anecdotal evidence from educators suggest that classroom peers play a meaningful role in how students learn. However, the literature has failed to consider the dynamic and context-dependent nature of classroom peer influence. Developmental psychology theories suggest that peer influence will increase and family influence will decrease as children enter adolescence. This study uses rich administrative data from North Carolina in 2006 to 2012, matching students to all peers in each of their courses in third through eighth grades. The analysis identifies trends in the magnitude of classroom peer effects across grade levels, with special attention to controlling for confounding factors such as simultaneous influence, student–classroom sorting, nonlinearity, and school-type effects. Consistent with psychological theories about adolescence, our findings indicate that the effect of average peer quality multiplies by a factor of nearly 3 for reading and 5 for math between fourth grade and seventh grade; contemporaneously, family socioeconomic status effects on academic performance nearly vanish by the end of middle school. We uncover additional evidence that ability grouping, while often harmful in an elementary school setting, becomes increasingly beneficial in later grades—particularly for math subjects.